Chapter La signoria rurale e le trasformazioni economiche della fine del medioevo (area lombarda e Italia centro-settentrionale). Qualche riflessione - POLONI, ALMA (Reti Medievali E-Book, 2023)
The lack of adequate historiographical insights has cast a negative light on the role of lordship in the late medieval economy; it has traditionally been seen as an obstacle to the free expression of market forces and thus to growth. While not endorsing this dated view, neo-institutionalist models have in fact reiterated this negative judgement. This article puts forward an interpretive proposal aimed at nuancing the image of lordship as an economically regressive force and reconsidering its role in late medieval growth processes.